Long-term exposure to environmental concentration of dinotefuran disrupts ecdysis and sex ratio by dysregulating related gene expressions in Chironomus kiinensis - Wei, Fenghua; Wu, Shuangxin; Li, Long (Frontiers in Endocrinology, 2024)
Currently, although there have been a few reports on the endocrine disrupting effects of neonicotinoids, yet this effect on Chironomidae during long-term exposure remains unknown. Here, ecdysis and sex ratio, along with ecdysone relevant gene expressions of representative neonicotinoid dinotefuran on Chironomus kiinensis were investigated at environmental concentrations by long-term exposure. Low dose of dinotefuran delayed pupation and emergence via inhibiting ecdysis. Sex-ratios of adults shifted toward male-dominated populations with the concentration of dinotefuran increasing. The corresponding transcriptions of ecdysis genes, ecr, usp, E74, and hsp70 were significantly downregulated in the midge. For estrogen effects, the vtg gene expression was upregulated but no significant change for err gene. These results would improve our understanding of the endocrine disrupting mechanisms of neonicotinoid insecticides to Chironomidae and provide data support for assessing their potential environmental risks.